Implementation of PhET Virtual Laboratory Media-Based Physics Learning on The Progress of Student Concept Mastery During the Covid-19 Pandemic - Florentina Maria Panda; Bonefasius Yanwar Boy (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2021)
This research aims to analyze the progress of mastery of the concept of Work & Energy and the concept of Dynamic Electricity with the application of media-based learning in the Virtual PhET laboratory. This type of research uses descriptive research to describe the object studied against the sample, namely students of the physics education study program, FKIP University of Cenderawasih. Collecting research data using a concept mastery test instrument given at the end of the lecture through a written essay test with 9 questions. This test is given to determine the mastery of students' concepts after taking lessons on the concepts of Work & Energy, and Dynamic Electricity. The test result data were analyzed based on the student's concept mastery assessment score. The results of the research obtained for concepts 1 and 2 mostly obtained very good and good categories of 63.50%, sufficient percentage category of 12.00%, and less and very poor categories of 21.00%. Therefore, the application of learning concept 1 and concept 2 based on the Virtual PhET laboratory media during the covid-19 pandemic for Cendrawasih University physics education students progressed to better mastery of concepts with the largest gains in the good and very good categories.